The Geoeconomics Analysis of the Digital Currency Law in El Salvador - Yuliana, Lidia Eka; Iswardhana, Muhammad Ridha (IHSA Institute, 2024)
The exclusive reliance of El Salvador is on the utilization of US Dollars for its day-to-day financial transactions. The review conducted in this research adopts geoeconomics of analysis to delve into the policy implications of integrating digital currency in El Salvador. This nation being the pioneer in embracing digital-based currency as an official medium of exchange, operates as local currency at present. The methodology employed in this research involves a qualitative-descriptive approach coupled with the collection of secondary data. The findings of this study indicate that the utilization of digital currency presents a dual nature due to its volatile characteristics, encompassing numerous advantages as well as disadvantages. Owing to the resolute implementation right from the beginning, the initiative undertaken by El Salvador poses both advantages and risks with regard to the legalization policy concerning digital currency